PHYTOCHEMICAL ANALYSIS OF COFFEE BY-PRODUCTS: SARAWAK LIBERICA COFFEE SILVERSKIN AND COFFEE LEAVES - Elexson, Nillian; Bryan Voon, Li Qi; Nick Laurence, Buyong; WENNY, SUNARHARUM; TUNJUNG, MAHATMANTO (UMT Press, 2025)
Coffee Silverskin (CS) and the leaves are by-products generated during the harvesting of green coffee beans. CS and the leaves obtained from the major Liberica species cultivated in Sarawak, Malaysia, remain underexplored. This study investigated the bioactive compound composition of Sarawak Liberica coffee silverskin and leaf extracts using gas chromatography coupled with mass spectrometry (GC-MS). Phytochemical analysis was conducted on the extracts of both CS and leaves. The GC-MS analysis revealed the presence of 41 chemical compounds, with four major compounds identified:5-hydroxymethylfurfural (5-HMF), D-allose, 1,6-anhydro-β-D-glucofuranose, and caffeine in the CS extract. The results indicated that the percentage of caffeine content in the CS extracts showed no significant difference (p < 0.05) between ethanol (1.55± 0.47%), methanol (1.77 ± 0.38%), and water (1.92 ± 0.65%). Additionally, the total phenolic content (TPC) of Liberica coffee leaves was measured at 35.76 ± 2.12 mg GAE/g extract, while the total flavonoid content (TFC) was 605.85 ± 8.20 mg QE/g extract. The antioxidant activity of Liberica coffee leaves was recorded at 54.37 ± 0.10%. The substantial presence of bioactive compounds suggests potential applications in food and pharmaceutical formulations.